Comparison of Two Types of Combined Measures, STI and U50, for Predicting Speech Intelligibility in Classrooms - CHOI, Young-Ji (Archives of Acoustics, 2017)
The present study reports on the speech intelligibility as measured by speech transmission index (STI) and useful-to-detrimental sound ratios (U_50) in university classrooms. Acoustic measurements were made in 12 quietly occupied university classrooms. The measured impulse responses of the classrooms were used to determine the modulation transfer function, m(F), for the STI calculation according to IEC 60268-16. U_50 values were determined from both signal-to-noise ratios (SNR) and C_50 values. The mean STI and frequency-weighted U_50 values for the 12 occupied classrooms were strongly linearly related. The results showed that classrooms with U_50 values of about +0.5 dB correspond to STI values of 0.60, indicating ‘good’ acoustical conditions for speech intelligibility. The results illustrate that the U_50 measure can be a more practically useful means of assessing and understanding room acoustics conditions for real speech communication in active classrooms.